EUROPEAN STANDARDS FOR CRISIS MANAGEMENT OF PUBLIC FINANCES - Goncharenko M.V. (Pressing Problems of Public Administration, 2016)
The article investigates European standards crisis management of public  nances and substantiatеs the rationale for the introduction of a number of  scal rules in Ukraine to improvement of public finances.